Implementation of Video-Based Science Teaching Materials to Improve Elementary School Students' Learning Outcomes - Siti Rosnawati; Siti Mayang Sari; Akmaluddin Akmaluddin (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to implement video-based science teaching materials to improve the learning outcomes of elementary school students. The research method used is a quantitative descriptive method. Science teaching materials combined with contextual learning videos to visualize abstract concepts provide a pleasant learning impression for students. Data were obtained through student response questionnaire sheets related to learning through the implementation of learning videos and learning outcome tests (pretest–posttest). The results showed that the science video teaching materials obtained a score with an implementation test and student response test obtained an average of 89% and the teacher's response as a learning observer was 89%, which means that the science learning videos are easy to use and interesting. From the effectiveness aspect, the increase in learning outcomes by getting an average pretest score of 68, posttest 84, resulting in an N-gain of 0.50. This proves that video-based science teaching materials are effective in improving the learning outcomes of elementary school students with science lessons.